Application of Some Fixed-Point Theorems in Orthogonal Extended S-Metric Spaces - Mohammad Mahdi Rezaei (Hindawi Limited, 2021)
In this study, we obtain some coincidence point theorems for weakly O-α-admissible contractive mappings in an orthogonal extended S-metric space. An example and an application are provided to illustrate the usability of the obtained results. Our results generalize the results of several studies from metric and S-metric frameworks to the setting of orthogonal extended S-metric spaces.